Análise da segurança e saúde do trabalho em empresas de pré-fabricado de concreto utilizando princípios da engenharia de resiliência - Moreira, Fabiano Tofolli (2011)
The Safety and Health at Work (SHW) management is recognized as one of the main factors so the enterprises may be able to fulfill their basic goals of coast, term and quality. One of the latest management strategies is the Resilience Engineering (RE) approach that considers the presence of four main principles for appliance: Top Management Commitment, Apprenticeship, Flexibility and Consciousness. Considering the intensive use of the concrete precast building systems it becomes substantial to study this section about the SHW aspects on the RE focus and record the good practices held by the companies. This work is based on the proposal elaborated by Costella (2008) which presents an Evaluation Method of the Safety and Health at Work based on the safety management principles and the RE. The case study method was adopted, a concrete precast producer enterprise was searched, which had a qualified management system, and it accepted to collaborate with the research. It was concluded that the researched Enterprise presents evidence of the application of the RE principles, mainly due to the existence of the SHW management. It was verified that there are ordinary and complementary concerns, such as the operation of critical sectors and the maintenance of the equipment currently used in factories and construction sites.